Clinical and parasitological evaluation of dogs naturally infected by Leishmania (Leishmania) chagasi submitted to treatment with meglumine antimoniate and allopurinol - Ikeda-Garcia, Fabiana Augusta [UNESP]; Lopes, Raimundo Souza [UNESP]; Marques, Fábia Judice; Ciarlini, Paulo César [UNESP]; Lima, Valéria Marçal Félix de [UNESP]; Morinishi, Celina Kazue; Zanette, Maurício Franco; Perri, Silvia Helena Venturoli [UNESP]; Marcondes, Mary [UNESP] (My University, 2010)
Aiming to assess the efficacy of the treatment, to verify the occurrence of possible disease relapses and to search for the presence of parasites after the treatment, seven dogs naturally infected by Leishmania sp., were submitted to a treatment with meglumine antimoniate and allopurinol. For this, lymph node and bone marrow aspiration biopsies were carried out at seven moments. After the end of the six-month observation period all dogs were submitted to euthanasia. Then, spleen and liver “imprints” and in vitro cultures were carried out to search for amastigote forms of the parasite. All animals presented remission of the symptoms and during all the observation period no dog presented relapse of the disease, although amastigote forms of the parasite were observed in two of the animals at the end of the experiment. Thus, it was possible to conclude that the treatment promotes clinical healing but it does not eliminate the parasites completely.

Com objetivo de avaliar a eficácia do tratamento, verificar a ocorrência de possíveis recidivas da doença e pesquisar a presença de parasitas após a realização do tratamento, foram utilizados sete cães naturalmente infectados por Leishmania sp., submetidos a tratamento com antimoniato de meglumina e alopurinol. Para tanto, foram realizadas punções biópsias aspirativas de linfonodos e de medula óssea em sete momentos. Após o término dos seis meses de observação, todos os cães foram submetidos à eutanásia e realizados “imprints” e cultivo in vitro do baço e fígado para a pesquisa de formas amastigotas. Todos os animais apresentaram remissão dos sintomas e durante todo o período de observação nenhum cão apresentou recidiva da doença apesar de ter sido observada a presença de formas amastigotas do parasita em dois animais, ao término do experimento. Desta forma, foi possível concluir que o tratamento promove a cura clínica, entretanto não elimina completamente os parasitas.
Avaliação clínica e parasitológica de cães naturalmente infectados por Leishmania (Leishmania) chagasi submetidos a tratamento com antimoniato de meglumina e alopurinol
Keywords: Dogs; Visceral leishmaniasis; Treatment; Allopurinol; Meglumine antimoniate; Cães; Leishmaniose visceral; Tratamento; Alopurinol; Antimoniato de meglumina